TGFB1 +869 T > C (rs1800470) variant is independently associated with susceptibility, laboratory activity, and TGF-β1 in patients with systemic lupus erythematosus - Nicole Perugini Stadtlober; Tamires Flauzino; Lorena Flor da Rosa Franchi Santos; Tatiana Mayumi Veiga Iriyoda; Neide Tomimura Costa; Marcell Alysson Batisti Lozovoy; Edna Maria Vissoci Reiche; Andréa Name Colado Simão (Taylor & Francis Group, 2021)
The aim of this study was to evaluate the association of the +869 T > C (rs1800470) and −509 C > T (rs1800469) TGFB1 variants, individually or in haplotypes structure, with susceptibility, autoantibodies, disease activity, and TGF-β1 plasma levels in patients with systemic lupus erythematosus (SLE). The study included 203 patients with SLE and 165 healthy controls. TGFB1 variants were determined by real-time polymerase chain reaction (qPCR). Plasma levels of TGF-β1 were determined using immunofluorimetric assay. The TGFB1 + 869 CC genotype was associated with SLE susceptibility (OR: 1.710, 95%CI: 1.020-2.866, p = 0.042) and with reduction of C4 (p = 0.040) and TGF-β1 levels (p = 0.044). In addition, patients with TGFB1 + 869 TC and CC genotypes and positive anti-dsDNA had lower TGF-β1 levels than those with TT (p = 0.004). TGFB1 −509 TT genotype was associated with reduced levels of C4 (p = 0.032). There was no association between haplotypes and clinical and laboratory parameters. Our data demonstrated that the TGFB1 + 869 T > C variant could be used as a genetic marker for SLE susceptibility and both variants as predictors of laboratory activity. This is the first study to demonstrate that TGF-β1 levels could be modulated by the interaction between TGFB1 + 869 C allele, in homozygosity, or heterozygosity, and the presence of anti-dsDNA.